BIOFUNCTIONAL PROPERTIES OF MILK FAT GLOBULE MEMBRANE PHOSPHOLIPIDS - Smoczyński, Michał (Polish Journal of Natural Sciences, 2023)
The aim of the paper is to discuss the general properties of polar lipids present in the milk fat globule membrane (MFGM), their role in living organism and some benefits of consuming these components in the human diet. Milk phospholipids contain glycerophospholipids and sphingolipids. These compounds perform a multitude of functions in living organisms: they serve as energy storage for the body, are a building blocks of cell membranes, they and their derivatives are bioactive molecules involved in the mediation and recognition of signals, and interact with other cell components. There has been an increasing number of reports documenting the health benefits of milk lipid consumption. Although they are present in milk in small quantities, their unique properties may help prevent and alleviate numerous diseases.